Osteoarthritis Is Associated With an Increased Risk of Age-Related Macular Degeneration: A Population-Based Longitudinal Follow-Up Study - Chiu, Yi-Hsiang; Huang, Jehn-Yu; Huang, Ya-Ping; Pan, Shin-Liang (Frontiers in Medicine, 2022)
Aims: To investigate the long-term risk of age-related macular degeneration (AMD) in persons with osteoarthritis (OA). Methods: This retrospective cohort study first enrolled 71,609 subjects diagnosed with OA, and 236,169 without such a diagnosis between January 1, 2002 and December 31, 2005, from the Longitudinal Health Insurance Database 2005. All were aged 40 to 69. After excluding subjects who had pre-existing AMD and/or who had missing socioeconomic data, frequency matching by sex and age was performed. This resulted in there being 60,274 subjects in each of the final matched OA and non-OA groups. The study participants were followed up to the occurrence of AMD, death, or the end of 2011. We used Cox proportional-hazards regression to estimate the impact of OA on the risk of developing AMD, and performed subgroup analyses stratified by sex and age. Results: The median follow-up time was 8.9 years, with an interquartile range of 1.4 years. The incidence rate of AMD in the OA group was 2.77 per 1,000 person-years (95% confidence interval [CI], 2.62–2.92), and in the non-OA group, 2.06 per 1,000 person-years (95% CI, 1.94–2.19). The adjusted hazard ratio (HR) of AMD for the OA group was therefore 1.30 (95% CI, 1.20–1.41). In the subgroup analysis stratified by sex for the OA group, the adjusted HRs of AMD were 1.29 in the women’s stratum and 1.31 in the men’s. When stratified by age, the adjusted HRs of AMD for the younger (40–54 years) and older (55–69 years) strata were 1.28 and 1.31, respectively. Conclusions: Persons with OA have an increased risk of developing AMD, regardless of age and sex.